(untitled) (ACME, 2021)
This paper offers an update and a revision of the replica series related to the Resting Herakles schema in its typological declinations “Farnese” and “Caserta”. The thirteen colossal sculptures belonging to these sequences show so many mutual affinities in terms of composition and format that the use of mechanical methods of reproduction is evident. The dimensional range of these statues is invariably between 290 and 300 cm, almost equivalent to a 10-feet modulus in ancient measurement systems. This correspondence allows a number of considerations regarding not only the reciprocal relations between the two types, but also the notion of “colossality” within Greek and Roman sculptural production.